An active shrinkage and antioxidative hydrogel with biomimetic mechanics functions modulates inflammation and fibrosis to promote skin regeneration - Tao Zhang; Xin-Cao Zhong; Zi-Xuan Feng; Xiao-Ying Lin; Chun-Ye Chen; Xiao-Wei Wang; Kai Guo; Yi Wang; Jun Chen; Yong-Zhong Du; Ze-Ming Zhuang; Yong Wang; et al. (Bioactive Materials)
Achieving scar-free skin regeneration in clinical settings presents significant challenges. Key issues such as the imbalance in macrophage phenotype transition, delayed re-epithelialization, and excessive proliferation and differentiation of fibroblasts hinder wound healing and lead to fibrotic repair. To these, we developed an active shrinkage and antioxidative hydrogel with biomimetic mechanical functions (P&G@LMs) to reshape the healing microenvironment and effectively promote skin regeneration. The hydrogel's immediate hemostatic effect initiated sequential remodeling, the active shrinkage property sealed and contracted the wound at body temperature, and the antioxidative function eliminated ROS, promoting re-epithelialization. The spatiotemporal release of LMs (ACEI) during the inflammation phase regulated macrophage polarization towards the anti-inflammatory M2 phenotype, promoting progression to the proliferation phase. However, the profibrotic niche of macrophages induced a highly contractile α-SMA positive state in myofibroblasts, whereas the sustained LMs release could regulate this niche to control fibrosis and promote the correct biomechanical orientation of collagen. Notably, the biomimetic mechanics of the hydrogel mimicked the contraction characteristics of myofibroblasts, and the skin-like elastic modulus could accommodate the skin dynamic changes and restore the mechanical integrity of wound defect, partially substituting myofibroblasts' mechanical role in tissue repair. This study presents an innovative strategy for skin regeneration.